Penyuluhan Pendanaan di Luar Neraca (Off-Balance-Sheet Financing), Modal Saham, dan Saldo Laba bagi Karyawan Bidang Akuntansi - Novyarni, Nelli; Harni, Reni; Kartijo, Kartijo; Luthfi, Muhammad; Rahayu, Dwi; Setiawan, Muhammad Rizki (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This activity aims to provide counseling on off-balance sheet financing techniques for accounting employees at STEI Jakarta. The method used in this activity is counseling based on processing materials delivered by competent speakers. The results of this community service activity indicate that participants are able to understand the importance of off-balance sheet financing counseling techniques, share capital and retained earnings for accounting employees. In addition, participants also gain an understanding of managing and organizing financial funding more efficiently and effectively.